(untitled) - Gifford, G. Barry (Lausanne (Switzerland), 1968)
This book major is presented about the beach to the north of the castle, the castle seen from the east, paln of Chillon, the castle seen from the south,...
Keywords: Château de chillon (veytaux, switzerland); Guidebooks